QTL MAPPING FOR SOME IMPORTANT DROUGHT TOLERANT TRAITS IN UPLAND COTTON - M. A. Saleem; T. A. Malik; A. Shakeel; M. Ashraf (Journal of Animal and Plant Sciences, 2015)
Drought stress is a major factor limiting crop production. Genetic improvement is possible in cotton and other crops against drought stress by molecular breeding. A drought tolerant (B-557) and a drought susceptible (FH-1000) cultivar were crossed to develop F2 population. The parents and the F2 population were studied under osmotic stress in hydroponic culture. A survey of 524 SSR and EST-SSR primers revealed a lot of DNA polymorphism between the drought resistant and drought susceptible cultivar. The polymorphism was used to construct genetic linkage map using the F2 population. In linkage analysis, 22 primers were mapped on chromosomes. Two QTLs for relative water content were identified. One QTL was mapped on chromosome 23 with nearest marker NAU2954 and another QTL was mapped on chromosome 12 with nearest marker NAU2715. One QTL for excised leaf water loss was found on chromosome 23 with nearest marker NAU2954. These QTLs may be used in molecular breeding program to develop drought tolerant cotton cultivars.
Keywords: Cotton; drought; relative water content; excised leaf water loss; cell membrane stability; QTL